Non-intubated thoracic epidural anesthesia for modified radical mastectomy as an alternative to general anaesthesia - Sa??ro?lu, Gönül; Sezer, Atakan; Cakcak, Ethem; Çopuro?lu, Elif; Sagiroglu, Tamer; Hekimoglu, S (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2018)
Purpose: We provide the application of modified radial mastectomy in perioperative treatment under awake thoracic epidural block in breast cancer operations. Methods: Twelve women who underwent modified radical mastectomy in elective breast cancer surgery were included in the study. All patients were treated without tracheal intubation using thoracic epidural anesthesia and sedation. The epidural catheter was placed in the T 4-5 level and the mixture of 0.5% bupivacaine and fentanyl was gradually administered with careful haemodynamic monitoring. Target-controlled propofol infusion was used. Pain intensity was evaluated by using a 10 cm VAS, where zero represented no pain and 10 cm represented worst possible pain. The primary endpoint was pain. A VAS score of 4 cm or less was considered to be an acceptable level of pain. The sedation situation was focused and calm in Wilson 2 level and in cooperation with sedation. Preoperative comorbidity and perioperative therapy were recorded. Results: We observed 4 hypotensive patients treated by increasing intravenous fluid infusion rate and initiating dopamine infusion. One patient had bradycardia, one patient had nausea and three patients had vomiting. There were no respiratory complications or pruritus. The mean duration of hospitalization is 5 days postoperatively. The patient had no intraoperative or postoperative complications. Conclusion: Epidural block in axillary lymph node dissection and oncologic mastectomy may be considered as a safe anesthetic option.